Pengaruh Terpaan Media Live Shopping Tiktok Terhadap Keputusan Pembelian @theoriginote - Wirawan Akbar; Velda Ardia Murdiana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The Originote is a skincare brand that was founded in 2022 and the product that made this brand boom is its moisturizer. This research aims to identify the influence of exposure to determine purchasing decisions for The Originote as a new skincare brand. where this research uses quantitative methods which are accompanied by data collection techniques using structured questionnaires and assisted by documentation as complementary evidence. The aim of this research is to measure the influence of exposure to TikTok live shopping media on purchasing decisions. And how much influence it has. The theory used in this research is Media Exposure theory which includes Frequency, Attention and Duration, as well as purchasing decision theory which includes problem recognition, information search, alternative evaluation, purchasing decisions, and post-purchase behavior. This research uses a quantitative approach and survey research methods. The data collection technique was carried out by distributing questionnaires to 90 predetermined respondents. Sampling used a simple random sampling technique (lottery technique). This research is shown by the average value of respondents' answers for variable (X) of 4.305. This value is classified as high (agree) and the average respondent's answer for the variable (Y) is also classified as high (agree) at 4.36. The quite large influence of media exposure and purchasing decisions can also be seen in the correlation (R) value of 0.833 which is quite high and the R Square value of 0.694 or 69.4% is influential, while the remaining 30.6% is influenced by other factors.